Syndication in science: Curated collaboration - David B. Hurry; Elena S. Izmailova; Simon Davies; Olivier Harari; S. Aubrey Stoch; John A. Wagner (Clinical and Translational Science)
Abstract Development and validation of digital measures require dedicated clinical studies, which can be conducted by a single study sponsor or a precompetitive collaboration. In this perspective, we propose an alternative model, data syndication, a curated collaboration, which foresees a technology provider being a founding member with biopharmaceutical sponsors and other stakeholders joining. Its main advantages are the speed of the study startup and the opportunity for real‐time data streaming.